Genealogy and Transformation of Islamic Educational Institutions from Classical to Contemporary Periods - Herina Yanti; Junaidi Junaidi; Nasbin Panyahatan (Ahlussunnah: Journal of Islamic Education, 2026)
This article analyzes the genealogy of Islamic Education institutions in Indonesia to examine their historical dynamics and transformation issues within political, social, and educational contexts. The study is motivated by a gap in the existing literature, which tends to be descriptive and insufficiently addresses power relations in the institutionalization process of Islamic education. This research employs a qualitative research design using a content analysis approach, combined with historical-critical analysis and social hermeneutics. The data sources include historical records, policy documents, and academic literature related to the development of Islamic education institutions from the pre-colonial period to the contemporary era. The findings indicate that the institutionalization of Islamic education has unfolded in a non-linear and dialectical process between Islamic educational traditions (ribath, halaqah, and pesantren) and state intervention through madrasah formation and integration into the formal education system. This process is shaped by power relations among religious authorities, the state, and global modernization forces. The study reveals an epistemological tension in the institutionalization of Islamic education, particularly between the authenticity of Islamic values, state agendas, and market-driven educational demands. This study emphasizes the need for a genealogical reconstruction to reformulate the direction of Islamic education development in Indonesia in a more critical, contextual, and adaptive manner toward contemporary social changes.